2014
DOI: 10.1080/01635581.2014.894102
|View full text |Cite
|
Sign up to set email alerts
|

Fish Consumption and Lung Cancer Risk: Systematic Review and Meta-Analysis

Abstract: There is evidence pointing to a possible role of diet on cancer etiology. Prior studies evaluating the relationship between fish consumption and lung cancer risk reported inconclusive results. The aim of this study was to achieve a comprehensive assessment of the relationship between fish consumption and lung cancer risk through systematic review and meta-analysis. Case control and cohort studies up to September 1, 2012 about fish consumption and lung cancer risk were confirmed by an online search. Separate re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 52 publications
2
31
0
Order By: Relevance
“…A recent review on heme iron and lung cancer risk reported that from the total number of studies evaluating heme iron intake and lung cancer risk, only two studies used a specific food composition database [33, 34]. Second, different animal sources of heme iron such as poultry or fish have been associated with a decreased lung cancer risk [35, 36], whereas red meat is associated with an increased risk [33]. In the current investigation, we adjusted for red meat; therefore, it can be speculated that the observed beneficial role of heme iron may be due to other animal dietary sources.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review on heme iron and lung cancer risk reported that from the total number of studies evaluating heme iron intake and lung cancer risk, only two studies used a specific food composition database [33, 34]. Second, different animal sources of heme iron such as poultry or fish have been associated with a decreased lung cancer risk [35, 36], whereas red meat is associated with an increased risk [33]. In the current investigation, we adjusted for red meat; therefore, it can be speculated that the observed beneficial role of heme iron may be due to other animal dietary sources.…”
Section: Discussionmentioning
confidence: 99%
“…There is conflicting evidence regarding the impact of exogenous hormones among women, diet, and BMI, on lung cancer risk 4047 . Moreover, there are limited studies that have assessed potential racial and ethnic differences for these established and putative risk factors lung cancer risk factors.…”
Section: Cigarette Smokingmentioning
confidence: 99%
“…As one important component of diet, fish is considered to be quite healthy, which has been found to be associated with lower risk of all-cause mortality [9], cardiovascular diseases [10] and stroke [11], as well as some forms of cancer, including colorectal [12], lung [13], prostate [14], breast [15], and liver cancers [16]. However, the association between fish intake and brain cancer risk is still inconclusive and inconsistent, and the evidence is scattered.…”
Section: Introductionmentioning
confidence: 99%